Satisfaction with life and its relationship to future anxiety among a sample of Benghazi University students - المصراتي ندى; الرفادي أحلام (Scientific Journal of University of Benghazi, 2021)
The current study aimed to identify the nature of the correlation between life satisfaction with and anxiety of the future a simple of Bengahzi University students. to identify And the level of each variable of the study, also knowing the differences related to (gender - specialization) in both variables. The study has been made available from (140 students) from Bengahzi University students.Two instruments were used to collect the data, The study found high level of life satisfaction and high level of future anxiety Also there were no relationship between the two variables the study suggested some recommendations.